Taking another look at policy research on China’s accession to the World Trade Organization - Ianchovichina, Elena; Martin, Will (World Bank, 2019)
Recent work on China’s accession to the World Trade Organizations pays little attention to the wave of reforms in China in the 1980s and 1990s. These reforms created the preconditions for accession and strongly influenced its outcomes. The preeminence of processing trade at the time of accession sharply reduced the impact of accession-related tariff reductions on exports and set the stage for China’s increases in domestic value added and reduction in China’s involvement in global production sharing since that time. The assessment in this paper, based on export data and simulation results on the ex ante accession-related effects on export volumes in the literature, finds that the accession must have increased China’s real export growth by at most is substantial, but not as large as suggested by the difference between the pre- and post-accession export growth rates in the four years before and after accession. This is because the influence of cyclical fluctuations related to the Asian financial crisis and the U.S. dot-com crash dampened export growth in the period before accession in 2001 and accelerated it afterward.